ANALYSIS OF COMPETENCE AND REWARD ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT PT PLN (PERSERO) CUSTOMER SERVICE IMPLEMENTATION UNIT PEMATANGSIANTAR - Posma Julyarto Sihombing; Muhammad Isa Indrawan; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the effect of competence and rewards on employee performance with work discipline as an intervening variable at PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Pematangsiantar. The background of this research is based on the importance of employee performance in achieving the company’s performance targets, particularly in providing the best service to customers through improving competence, giving rewards, and enhancing employee work discipline. This research employs a quantitative approach with a population of 80 meter-reading employees working at PT PLN (Persero) UP3 Pematangsiantar, determined as a saturated sample. Data analysis was carried out using Partial Least Square (PLS) through SmartPLS.